2004
DOI: 10.1897/03-491
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in mountain yellow‐legged frogs (Rana muscosa) from the Sierra Nevada Mountains of California, USA

Abstract: In 1997, pesticide concentrations were measured in mountain yellow-legged frogs (Rana muscosa) from two areas in the Sierra Nevada Mountains of California, USA. One area (Sixty Lakes Basin, Kings Canyon National Park) had large, apparently healthy populations of frogs. A second area (Tablelands, Sequoia National Park) once had large populations, but the species had been extirpated from this area by the early 1980s. The Tablelands is exposed directly to prevailing winds from agricultural regions to the west. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 35 publications
7
89
3
1
Order By: Relevance
“…From a landscape perspective, many of the water soluble herbicides (atrazine) were detected frequently in water and less frequently in sediment and tissues, whereas several more hydrophobic compounds (DDE, pyraclostrobin) were detected predominantly in sediment and more frequently in tissues (Table 3). Wetland sediment can be a sink for hydrophobic contaminants and our results support previous work documenting the bioaccumulation of agrochemicals in amphibians (Smalling et al, 2013b;Fellers et al, 2004). Frogs are exposed to pesticides in both the aquatic and terrestrial environments and in many cases wetland habitats where they are captured do not completely explain their contaminant body burdens.…”
Section: Occurrence Of Pesticides In Amphibianssupporting
confidence: 74%
“…From a landscape perspective, many of the water soluble herbicides (atrazine) were detected frequently in water and less frequently in sediment and tissues, whereas several more hydrophobic compounds (DDE, pyraclostrobin) were detected predominantly in sediment and more frequently in tissues (Table 3). Wetland sediment can be a sink for hydrophobic contaminants and our results support previous work documenting the bioaccumulation of agrochemicals in amphibians (Smalling et al, 2013b;Fellers et al, 2004). Frogs are exposed to pesticides in both the aquatic and terrestrial environments and in many cases wetland habitats where they are captured do not completely explain their contaminant body burdens.…”
Section: Occurrence Of Pesticides In Amphibianssupporting
confidence: 74%
“…However, without a solid understanding of host-pathogen dynamics and the biology of the host and pathogen in the landscape, translocations/reintroductions have little probability of success. Several attempts have been made to repatriate amphibians affected by chytridiomycosis in Europe, North America, the Caribbean and Africa but none have led to successful, long-term amphibian re-establishment [4,26,28,29] (but see [30] for evidence of shortterm post-release survival). Although the majority of failures have been associated with the re-emergence of lethal chytridiomycosis in the translocated/reintroduced species, the cause behind failure to re-establish in almost every case could not be attributed clearly [26,28] (but see [11]).…”
Section: Trialled and Testedmentioning
confidence: 99%
“…The most dramatic decline has been observed for the mountain yellow-legged frog (Rana muscosa), which has disappeared from more than 90% of its historic range in the Sierra Nevada [7]. Several hypotheses have been proposed to explain these declines, including the introduction of nonnative fish species [8], elevated levels of ultraviolet radiation [9], recent emergence of the chytrid disease [5], and increasing pesticide use in adjacent agricultural areas [10][11][12]. Davidson and Knapp [13] suggested that multiple stressors may be involved, although upwind pesticide application appears to have had the greatest influence on amphibian declines in the Sierras.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported pesticide concentrations in fish and amphibians [6,11,[14][15][16][17][18], although measurements of pesticides in the atmosphere and aquatic habitats are relatively sparse. Pesticide concentrations in wet deposition [19] and in air, dry deposition, and surface water [2] were measured in Sequoia and Kings Canyon National Parks (Fig.…”
Section: Introductionmentioning
confidence: 99%